Molecular Characterization of a Novel Budgerigar Fledgling Disease Virus Strain From Budgerigars in China - Hu, Xiaoliang; Cai, Dongdong; Liu, Siru; Li, Yan; Chen, Lulu; Luo, Guangmei; Pu, Hongli; He, Yucan; Liu, Xiangxiao; Zhao, Lili; Cao, Hongzhi; Yang, Tiankuo; et al. (Frontiers in Veterinary Science, 2022)
Budgerigar ﬂedgling disease virus (BFDV) is the causative polyomavirus of budgerigar ﬂedgling disease, an important avian immunosuppressive disease in budgerigars (Melopsittacus undulatus). In the current study, we explored the etiological role and molecular characteristics of BFDV. We identified a novel BFDV strain, designated as SC-YB19, belonging to a unique cluster with three other domestic strains (WF-GM01, SD18, and APV-P) and closely related to Polish isolates based on complete sequences. Sequence analysis showed that SC-YB19 had an 18-nucleotide (nt) deletion in the enhancer region, corresponding to the sequence position 164–181 nt, which differed significantly from all other BFDV strains. Based on sequence alignment, three unique nucleotide substitutions were found in VP4 (position 821), VP1 (position 2 383), and T-antigen (position 3 517) of SC-YB19, compared with APV-7, AF241168, AF241169, AF241170, M20775 and NC004764. These results demonstrate that BFDV genotype variations are co-circulating in China, thus providing important insight into BFDV evolution.